Adverse Life Events: Do Home Care Clients Have Resources for Mastering Them? - Garms-Homolová, Vjenka; Declercq, Anja; Finne-Soveri, Harriet; Notthoff, Nanna; van der Roest, Henriëtte G.; van Hout, Hein P. J. (Frontiers in Medicine, 2021)
Objectives: Research on adverse life events has a long tradition. Few studies have addressed this topic in connection to very old people. Life stressors, especially major life stressors (MLSs) experienced by clients of home care services in the community have rarely been the subject of studies. Considering this gap, we investigated the prevalence of MLSs in home care clients. We examined the effects that MLSs have on their mood and health status as well as the impact of clients’ social resources on MLSs and their outcomes. Method: We used assessment data from 2,884 home care clients in six European countries. The methodological basis was the standardized interRAI Home Care Assessment (interRAI HC). Results: 15.4% of the sample – women and men with an average age of 82.89 years - experienced an MLS in the last six months before the assessment. They were more depressed than persons without these experiences, and their health status indicated a higher level of instability and deterioration. At reassessment after six months, the situation changed. Despite the fact that both outcomes of the MLSs, depression and health status became worse in the reassessment-sample, home care clients without MLS were more affected by the worsening, especially that of depression. The expected buffering impact of social resources was low. Discussion: Although this study worked with limited information on MLSs, it could contribute to closing various knowledge gaps. The study shows that the MLSs represent a prevalent problem in a population of home care clients and that this problem has negative consequences on their mood and stability of their health status. This research took up the situation of very old and vulnerable adults, who have previously rarely been considered in studies on major critical life events and stressors. Conclusion and research perspective: Future research on MLSs has to take up the issue of the time passage between the MLS and the impact on health and well-being of individuals dependent on care. It has to determine immediate as well as later consequences and identify those factors that are appropriate to reduce the MLS-effects on very old people dependent on care.